Nanoclay effect on the ablative behaviour of glass fiber reinforced polymer and glass fiber reinforced geopolymer nanocomposite using radiography - Shauqi, Ilham; Yaacob, Izzat Najmi; Hua, Tay Chai; Muhammad Amir, Siti Madiha; Rahim, Sapizah; Umar, Mohd Zaki; Abu Bakar, Asyraf Arif; Kapilan, Natesan; Mazlan, Norkhairunnisa (The Aeronautical and Astronautical Society of the Republic of China, 2024)
The addition of nanoscale additives to polymers can increase their thermal resistance, making them suitable for a variety of engineering applications. In this investigation, nondestructive testing (NDT) was performed to observe the composite's post-fire test behaviour. This study investigated the ablative behaviour of glass fibre-reinforced epoxy and geopolymer with varying nanoclay concentrations. Additionally, after firing all of the samples, the thermal defects were evaluated with Infrared thermography method, Digital Detector Array (DDA) Radiography method. According to the ablation analysis, increasing the nanoclay concentration in nanocomposites was found to increase the samples' thermal ablation. In addition, geopolymer nanocomposite exhibited superior ablative behaviour compared to epoxy nanocomposite, with a back surface temperature of 51.34 °C compared to 176.86 °C for 7 wt nanoclay in epoxy nanocomposite. DDA analysis revealed that the nanocomposite surface structure contains fewer voids when a higher proportion of nanoclay is employed.